2016
DOI: 10.1039/c6ee00377j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interlayer anions on [NiFe]-LDH nanosheet water oxidation activity

Abstract: Water oxidation activity of nickel–iron layered double hydroxide ([NiFe]-LDH) nanosheet electrocatalysts is a function of interlayer anion basicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
394
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 492 publications
(419 citation statements)
references
References 49 publications
24
394
0
1
Order By: Relevance
“…TheO À Ce À Ovibration remained broad and shifted to lower wavenumber compared to commercial CeO 2 .X PS spectra also showed that the coexistence of Ce 3+ and Ce 4+ was retained, along with the coexistence of the oxide and hydroxide,a fter anodic polarization (Supporting Information, Figure S4 c,d). [5d] It is consistent with the claim in the literature that only limited amount of Fe was highly active sites [15] and those sites were lost, which could not be quantified by our ICP measurement. From ICP measurement, the amount of Fe in the bare NiFeO x remained unchanged after stability test (Supporting Information, Table S1) in contrast with the previous report observing content of Fe dropped from 50 % to 25 %.…”
Section: Angewandte Chemiesupporting
confidence: 91%
“…TheO À Ce À Ovibration remained broad and shifted to lower wavenumber compared to commercial CeO 2 .X PS spectra also showed that the coexistence of Ce 3+ and Ce 4+ was retained, along with the coexistence of the oxide and hydroxide,a fter anodic polarization (Supporting Information, Figure S4 c,d). [5d] It is consistent with the claim in the literature that only limited amount of Fe was highly active sites [15] and those sites were lost, which could not be quantified by our ICP measurement. From ICP measurement, the amount of Fe in the bare NiFeO x remained unchanged after stability test (Supporting Information, Table S1) in contrast with the previous report observing content of Fe dropped from 50 % to 25 %.…”
Section: Angewandte Chemiesupporting
confidence: 91%
“…The intercalated NO 3 − anion increases the interlayer distance respect to CO 3 2and it is easier to exchange by OH − , that is the main reactant for OER in alkaline. [110] The authors synthesized NiFebased materials with a wide variety of intercalated anions (NO 3 − , BF 4 − , Cl − , ClO 4 − , CO 3 2− , C 2 O 4 2− , F − , I − , PO 4 3− , SO 4 2− ) either by anion exchange of nitrate intercalated NiFe LDH or directly by PLAL. Therefore the authors attributed the enhanced activity to these effects.…”
Section: Nature Of Intercalated Anionsmentioning
confidence: 99%
“…[35][36][37] These steps strongly depend on the chemical nature of the catalyst. [35][36][37] These steps strongly depend on the chemical nature of the catalyst.…”
mentioning
confidence: 99%